The number of irrational roots of the equation,
( x − 1 ) ( x − 2 ) ( 3 x − 2 ) ( 3 x + 1 ) = 2 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( x − 1 ) ( x − 2 ) ( 3 x − 2 ) ( 3 x + 1 ) = 2 1
[ ( x − 1 ) ( 3 x − 2 ) ] [ ( x − 2 ) ( 3 x + 1 ) ] = 2 1
[ 3 x 2 − 5 x + 2 ] [ 3 x 2 − 5 x − 2 ] = 2 1
Let y = 3 x 2 − 5 x
[ y + 2 ] [ y − 2 ] = 2 1
y 2 − 4 = 2 1
y 2 = 2 5
y = 5 or y = − 5
Thus: 3 x 2 − 5 x = 5 or 3 x 2 − 5 x = − 5 . The first equation yields two real solutions: 6 5 + 8 5 and 6 5 − 8 5 . The second equation's discriminant is less than zero, so it has no real solutions.
Therefore, the equation ( x − 1 ) ( x − 2 ) ( 3 x − 2 ) ( 3 x + 1 ) = 2 1 yields 2 irrational roots altogether.
Problem Loading...
Note Loading...
Set Loading...
Upon expansion, the equation becomes
9 x 4 − 3 0 x 3 + 2 5 x 2 − 2 5 = 0 ⟹ ( 3 x 2 − 5 x ) 2 − 2 5 = 0 ⟹ ( 3 x 2 − 5 x + 5 ) ( 3 x 2 − 5 x − 5 ) = 0 .
Now 3 x 2 − 5 x + 5 = 0 yields no real, (and hence no irrational), solutions since the discriminant is less than zero.
With 3 x 2 − 5 x − 5 = 0 we have solutions x = 6 5 ± 8 5 , and so the answer is 2 .